2017
DOI: 10.1111/jcom.12313
|View full text |Cite
|
Sign up to set email alerts
|

Negative Stereotypical Portrayals of Muslims in Right-Wing Populist Campaigns: Perceived Discrimination, Social Identity Threats, and Hostility Among Young Muslim Adults

Abstract: Anti‐Islamic sentiments have become central to right‐wing populist mobilization in Western societies, which often results in negative portrayals of Muslims in political campaigns. Although these portrayals may have detrimental effects on minority members' identity formation and attitudes toward majority members, little is known about their effects on members of the depicted group. A lab experiment with 145 young Muslims reveals that right‐wing populist ad exposure increases perceived discrimination, which in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 64 publications
1
55
1
Order By: Relevance
“…The reason for this is negative implicit automatic associations, which may remain activated and unintentionally influence individuals’ behavioral intentions despite being explicitly rejected (Payne & Dal Cin, ). By openly and blatantly ostracizing immigrants and religious minority members such as Muslims (Schmuck et al, ), right‐wing populist parties tend to violate societal norms of tolerance and egalitarianism (Bos et al, ). Voters may therefore not openly agree with a party that employs simplistic campaign slogans and portrayals (Huber & Lapinski, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason for this is negative implicit automatic associations, which may remain activated and unintentionally influence individuals’ behavioral intentions despite being explicitly rejected (Payne & Dal Cin, ). By openly and blatantly ostracizing immigrants and religious minority members such as Muslims (Schmuck et al, ), right‐wing populist parties tend to violate societal norms of tolerance and egalitarianism (Bos et al, ). Voters may therefore not openly agree with a party that employs simplistic campaign slogans and portrayals (Huber & Lapinski, ).…”
Section: Discussionmentioning
confidence: 99%
“…Using a key principle of populist communication, a black and white rhetoric, right‐wing populist parties present simple solutions for people’s growing fears about increasing Muslim immigration: a total exclusion of Muslims from “the people.” This is a successful strategy—as growing vote shares for right‐wing populist parties across Europe demonstrate. However, while increasing their electoral support, right‐wing, populist campaign poster ads may also harm integration processes of Muslims in Western societies as a side effect (Schmuck et al, ). In particular, our finding that right‐wing populist posters may foster resentments against minority groups “under the radar” of conscious awareness seems alarming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are limited studies on the religious discrimination of Muslim minorities in the United States, but studies in the European context have revealed that religious discrimination may be particularly salient for Muslim minorities mental health, such as psychological distress, anxiety, depression, self‐esteem, and anger (e.g., Hassan, Rousseau, & Moreau, ; Jasperse, Ward, & Jose, ; Schmuck, Matthes, & Paul, ). However, more studies are needed to better understand the implications of religious discrimination in the United States given that evidence from Europe indicates that these relations depend on the sociocultural and sociopolitical context, including the compatibility of individuals’ religious and national identities (e.g., Kunst, Tajamal, Sam, & Ulleberg, ).…”
Section: Discrimination and Internalizing And Externalizing Problemsmentioning
confidence: 99%
“…This reaction to perceived disadvantage was originally attested in longitudinal studies among Ingrian-Finnish returnees from Russia and from the former Soviet Union (Jasinskaja-Lahti et al, 2009;Jasinskaja-Lahti, Mähönen, & Ketokivi, 2012;. Since then, the RDIM and closely related theorisations have continued to gain support in studies among Norwegian-Pakistani and German-Turkish Muslims (Kunst, Tajamal, Sam, & Ulleberg, 2012), Sunni Muslim immigrants of Turkish origin in Germany and the Netherlands (Maliepaard & Verkuyten, 2018), refugees in the Netherlands and Spain (Bobowik, Martinovic, Basabe, Barsties, & Wachter, 2017), first-generation Latino immigrants in the United States (Wiley, Lawrence, Figueroa, & Percontino, 2013) and in a laboratory study with an international sample of young Muslims (Schmuck, Matthes, & Paul, 2017), only to list some of the most recent.…”
Section: Theoretical Background Perceived Rejection Minority Identifmentioning
confidence: 97%